A 60 years old lady with osteomalacia due to deficiency of vitamin D - Azad, KAK; Karmaker, M; Sardar, MH; Mallik, MU; Appolo, AM; Islam, MS (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13248 J. Dhaka Med. Coll. 2012; 21(1): 116-119